2019
DOI: 10.1007/s10494-019-00039-7
|View full text |Cite
|
Sign up to set email alerts
|

LES Study of a Turbulent Spray Jet: Mesh Sensitivity, Mesh-Parcels Interaction and Injection Methodology

Abstract: This study focuses on Large Eddy Simulations (LES) in the Eulerian-Lagrangian framework of turbulent spray jets. The choice of the numerical grid relates both to turbulence level description and parcels-grid cells interaction. The objective of the present work is to determine a case setup capable of predicting flow fields of a turbulent n-heptane spray jet for which a set of experimental data in non-reactive conditions (isothermal) is available [21]. The study first focuses on the LES grid, based on simulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The topic enjoys renewed interest, prompted by the recent experimental investigation of Verdier et al [4] using Global Rainbow Thermometry to characterize the mean droplet temperatures in a complex lab-scale n-heptane spray flame. This flame was numerically investigated in the Workshop on Measurement and Computation of Turbulent Spray Combustion by different groups [5,6,7,8,9,10] using Lagrangian droplet models for the evaporating spray cloud. Specifically, Noh et al [6] compared various evaporation models following Miller et al [3], using large-eddy simulation (LES) to asses the droplet temperature predictions.…”
Section: Introductionmentioning
confidence: 99%
“…The topic enjoys renewed interest, prompted by the recent experimental investigation of Verdier et al [4] using Global Rainbow Thermometry to characterize the mean droplet temperatures in a complex lab-scale n-heptane spray flame. This flame was numerically investigated in the Workshop on Measurement and Computation of Turbulent Spray Combustion by different groups [5,6,7,8,9,10] using Lagrangian droplet models for the evaporating spray cloud. Specifically, Noh et al [6] compared various evaporation models following Miller et al [3], using large-eddy simulation (LES) to asses the droplet temperature predictions.…”
Section: Introductionmentioning
confidence: 99%
“…G. Daviller et al [2] demonstrated a new sensor and approach to effectively produce the desired local mesh refinement to match the target losses, which are measured experimentally. Utyuzhnikov et al [3] numerically simulated the combustion of fuel droplet vapor releases in the atmosphere and there are a number of studies that have been performed, especially on the use of LES methodology [4][5][6]. Jenft et al [7] experimented with a pool fire using water mist in comparison to a nozzle spray and droplet per second.…”
Section: Introductionmentioning
confidence: 99%